PENGARUH MOTIVASI KERJA, PENGEMBANGAN KARIR DAN JAM KERJA FLEKSIBEL TERHADAP DISIPLIN KERJA PEGAWAI - Seto Nurwidhiyanto; Syarif Ali (Jurnal Akuntansi dan Pajak, 2022)
This study is a quantitative study that aims to determine the impact of work motivation, career development, and flexible working hours on work dissipation at PT Karunia Mujur, Depok City. The population of this study were employees of PT Karunia Usaha Mujur, then the sample size was determined by 34 respondents using the saturated sample method and data collected using questionnaires via google form. The analytical technique applied is descriptive analysis technique and inferential analysis using the statistical test tool SMARTPLS 3.2.9. Meanwhile, the hypothesis test is t test and f test using a significance level of 5% (0.05). The results of this study show (1) there is no positive and insignificant effect between work motivation and work discipline; (2) there is a positive and significant effect between career development on discipline; (3) there is a positive and significant effect between flexible working hours on discipline; (4) Work motivation, career development, and flexible working hours simultaneously affect work discipline.